Association Between Risk Factors with The Event of Nasopharynx Carcinoma in Soebandi Hospital Period Of January 2017- March 2019 - Emda Zein Cik Fitria; Nindya Shinta Rumastika; Pipiet Wulandari (Journal of Agromedicine and Medical Sciences, 2020)
Abstract Nasopharyngeal carcinoma is the highest malignancy in the head and neck regio. The cause of nasopharyngeal carcinoma is unknown, but there are several risk factors that can trigger nasopharyngeal carcinoma which include age, gender, genetics, occupation, geographical location, consumption of salted fish, consumption of grilled fish / grilled meat, consumption of canned foods and smoking. This study aims to determine the risk factors that influence the incidence of nasopharyngeal carcinoma. The type of this study is a obervasional analysis with a case control design carried out on 40 samples that fulfilled the inclusion and exclusion criteria. The instrument of this research is in the form of medical record recapitulation and structured interviews. The bivariate test results were age (p=0.043), sex (p=1,000), genetics (p=0.044), occupation (p=0.740), geographical location (p= 1,000), consumption of salted fish (p = 0.004) , consumption of grilled fish / grilled meat (p=0.007), consumption of canned foods (p = 0.106) and smoking (p = 0.527). The multivariate test results were the consumption of salted fish with a value (p = 0.004), consumption of salted fish / grilled meat (p = 0.023), genetic (p = 0.062), and age (p = 0.264). The conclusion of this study is the consumption of salted fish, consumption of grilled fish / grilled meat, genetics and age have a significant relationship with the event of nasopharyngeal carcinoma and the most influential relationship is the consumption of salted fish. Keywords: nasopharyngeal carcinoma, risk factor, dr. Soebandi hospital